2018
DOI: 10.1007/s10278-018-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Stability and Discrimination Capacity of Radiomic Features on Apparent Diffusion Coefficient Images

Abstract: The objectives of the study are to develop a new way to assess stability and discrimination capacity of radiomic features without the need of test-retest or multiple delineations and to use information obtained to perform a preliminary feature selection. Apparent diffusion coefficient (ADC) maps were computed from diffusion-weighted magnetic resonance images (DW-MRI) of two groups of patients: 18 with soft tissue sarcomas (STS) and 18 with oropharyngeal cancers (OPC). Sixty-nine radiomic features were computed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 46 publications
(57 reference statements)
1
44
0
Order By: Relevance
“…This surrogate use of ROI translation is of course an approximation because modifications due to multiple segmentations are more random and complex to model. However, different previous studies of literature have shown how techniques based on image or ROI manipulation could be used to perform a preliminary feature selection instead of more traditional test (test-retest or multiple segmentation) with successful results, also in the application to clinical models [ 31 , 32 , 33 , 34 ]. For as far as the selection of features that were stable to the variations in the image acquisition parameters is concerned, that was performed based on the results of previous analyses on a virtual phantom representing the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This surrogate use of ROI translation is of course an approximation because modifications due to multiple segmentations are more random and complex to model. However, different previous studies of literature have shown how techniques based on image or ROI manipulation could be used to perform a preliminary feature selection instead of more traditional test (test-retest or multiple segmentation) with successful results, also in the application to clinical models [ 31 , 32 , 33 , 34 ]. For as far as the selection of features that were stable to the variations in the image acquisition parameters is concerned, that was performed based on the results of previous analyses on a virtual phantom representing the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Bologna et al [32] further suggests that ADC feature reproducibility will depend on the region of the body being examined. This suggests that repeatability and reproducibility should be considered early in the radiomic model development process, by way of a priori feature selection.…”
Section: Discussionmentioning
confidence: 99%
“…The fixed bin number method in which grey level intensities are discretized to a fixed number of bins allows for direct comparisons of RFs across multiple ROIs 30,32 . Based on our literature review 10,20 , the three widely used bin numbers of 32, 64 and 128 were assigned.…”
Section: Rf Calculationmentioning
confidence: 99%
“…The reliability of RFs also depends on the techniques used for lesion segmentation, grey-level discretization and quantization range 8,[15][16][17][18] . Therefore, failure in controlling such confounding factors may lead to inaccurate and unreliable RF estimation 9,15,[19][20][21][22] .…”
mentioning
confidence: 99%